Acanthosis Nigricans Associated with an Adrenocortical Tumor in a Pediatric Patient - Elizabeth Isaacoff; Filippina Filia Dimitriadi; Frank Barrows; Bruce Pawel; Peter Mattei; Sogol Mostoufi-Moab (Case Reports in Endocrinology)
Malignant acanthosis nigricans (AN) is a rare paraneoplastic syndrome seen primarily in adults with an underlying diagnosis of gastrointestinal adenocarcinoma. Malignant AN is characterized by hyperpigmentation and velvety hyperplasia of the epidermis. This condition is generally not associated with tumors in pediatric populations or in the adrenal gland. We present a case of malignant AN in a pediatric patient with a nonmalignant, functional adrenocortical tumor.